Fashion teaching in Brazil: between tracks and echoes (Revista de Ensino em Artes, Moda e Design, 2022)
Through the memories of teachers Dr. Maria de Fátima Mattos (CUML) and Dr. Mara Rúbia Sant'Anna (UDESC), the interview tells the story of the Forum of Fashion Schools Dorotéia Baduy Pires and the creation of the Working Group (WG) “Education: theory and practice in Fashion”, actions that take place during the Fashion Colloquium programming. The objective is to document the role of the Forum and the WG in the face of national transformations in the formation guidelines of fashion higher courses and to identify the potential of both for emerging curriculum changes, following the problems presented in the researches during the 1st WG Meeting, which mainly refer to the inclusion of diversities and the use of new technologies in teaching.
Keywords: Fashion Colloquium; Higher education; Fashion Schools Forum